Development and validation of ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method to quantify monotropein in blueberries - Ishveen Kaur; Courtney P. Leisner; Dennis P. Cladis (PLoS ONE, 2025)
Blueberries ( Vaccinium species) are an economically important fruit crop rich in bioactive compounds like polyphenols and flavonoids. Interestingly, some blueberry cultivars also produce monotropein, which has bioactive properties, including anti-inflammatory and neuroprotective effects. However, methods to quantify monotropein in blueberries have not been optimized. To address this gap, an optimized analytical method for monotropein extraction and quantification using ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) was developed. Different extraction strategies were compared, including variations in temperature, time, and ultrasonication treatments. Optimal extraction was achieved by heating samples to 60 °C for 15 mins in methanol. The method had high percent recovery and good repeatability. This protocol was then applied to 28 blueberry cultivars, 14 of which had not been previously analyzed for monotropein. Monotropein ranged from 0–1807 ng/mg dry weight. The developed method provides a robust tool that can be applied to future evaluations of monotropein in diverse blueberry cultivars.